Serum From Melioidosis Survivors Diminished Intracellular Burkholderia pseudomallei Growth in Macrophages: A Brief Research Report - Chaichana, Panjaporn; Kronsteiner, Barbara; Rongkard, Patpong; Teparrukkul, Prapit; Limmathurotsakul, Direk; Chantratita, Narisara; Day, Nicholas P. J.; Fletcher, Helen A.; Dunachie, Susanna J. (Frontiers in Cellular and Infection Microbiology, 2020)
Melioidosis is a neglected tropical disease with high mortality rate. It is caused by the Gram-negative, CDC category B select agent Burkholderia pseudomallei (B. ps) that is intrinsically resistant to first-line antibiotics. An antibody-based vaccine is likely to be the most effective control measure. Previous studies have demonstrated significant mechanistic roles of antibodies in protection against death in animal models, but data from human melioidosis is scarce. Herein, we used in-vitro antibody-dependent cellular phagocytosis and growth inhibition assays to assess the mechanism of protective antibodies in patients with acute melioidosis. We found that serum from patients who survived the disease enable more live B. ps to be engulfed by THP-1 derived macrophages (median 1.7 × 103 CFU/ml, IQR 1.1 × 103-2.5 × 103 CFU/ml) than serum from patients who did not survive (median 1.2 × 103 CFU/ml, IQR 0.7 × 103-1.8 × 103, p = 0.02). In addition, the intracellular growth rate of B. ps pre-opsonized with serum from survivors (median 7.89, IQR 5.58–10.85) was diminished when compared with those with serum from non-survivors (median 10.88, IQR 5.42–14.88, p = 0.04). However, the difference of intracellular bacterial growth rate failed to reach statistical significance when using purified IgG antibodies (p = 0.09). These results provide new insights into a mechanistic role of serum in protection against death in human melioidosis for antibody-based vaccine development.